Economic Evaluation for Peak Shaving of Wind Power Integrated System - Tingting Hou; Suhua Lou; Yaowu Wu; Zhilei Wang; Lin Yi (Institute of Advanced Engineering and Science, 2014)
The variable and non-dispatchable output of wind farms brings great difficulty to the quantitative analysis of the economic operation for peak shaving of power system integrated with high penetration of wind power. For the random nature of wind power, the paper establishes a peak shaving capacity requirement model for wind power. Based on the peak shaving capacity requirement model for wind power, a model for economy evaluation of peak shaving of power system with a high penetration of wind power is proposed. The model makes it possible to quantitatively analyze the influences of wind power integration on the peak shaving capacity requirement and operation economy. The case studies were carried out for a system, and the results verified the effectiveness and accuracy of the presented model. Some conclusions are summarized about the economy evaluation method of peak shaving of systems integrated with significant wind. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5096